Selib 1. preliminary report for the 2012 and 2013 seasons - Aneta Cedro (Polish Archaeology in the Mediterranean, 2016)
Part of a lower building was uncovered during the third and fourth seasons of excavationat the site of a church in Selib 1. Finds from the fill between floors confirmed the early dating ofthe oldest church (6th/7th century). Two buildings were examined in the vicinity of the innerperibolos: BN.13, which proved to be a domestic dwelling from a later phase (11th–12th century),and BS.13, identified as a structure of religious function built before the 9th–10th century.